2017
DOI: 10.1074/jbc.m116.774752
|View full text |Cite
|
Sign up to set email alerts
|

Identification and characterization of RNA aptamers: A long aptamer blocks the AMPA receptor and a short aptamer blocks both AMPA and kainate receptors

Abstract: AMPA and kainate receptors, along with NMDA receptors, represent different subtypes of glutamate ion channels. AMPA and kainate receptors share a high degree of sequence and structural similarities, and excessive activity of these receptors has been implicated in neurological diseases such as epilepsy. Therefore, blocking detrimental activity of both receptor types could be therapeutically beneficial. Here, we report the use of an in vitro evolution approach involving systematic evolution of ligands by exponen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
24
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(24 citation statements)
references
References 64 publications
0
24
0
Order By: Relevance
“…One group found a full-length aptamer that blocked AMPA receptors specifically, but a truncated version of the same aptamer equally inhibited both the AMPA and kainite receptors. [125,126], suggesting that the aptamer could serve multiple functions after truncation. Even though the dual function of this aptamer might be clinically beneficial, the functional or structural changes of aptamers after truncation should be carefully investigated.…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%
“…One group found a full-length aptamer that blocked AMPA receptors specifically, but a truncated version of the same aptamer equally inhibited both the AMPA and kainite receptors. [125,126], suggesting that the aptamer could serve multiple functions after truncation. Even though the dual function of this aptamer might be clinically beneficial, the functional or structural changes of aptamers after truncation should be carefully investigated.…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%
“…More precisely, no place shows a higher structural similarity than the site to which AB9 binds, although at the moment, we do not know where this site is. We do know, however, this site is a noncompetitive one [8] . It is highly likely that the "footprint" of AB9 site covers a larger surface area, which is needed to inhibit more selectively AMPA receptors.…”
mentioning
confidence: 99%
“…Expressing a single target, i.e., one protein or receptor, to maximize the surface expression and density as opposed to expressing multiple receptors with "diluted" surface density for any one of the targets would be an advantage for this approach. In a recent article in the Journal of Biological Chemistry by Jaremko et al 2017 [8] , we have reported such an approach for the discovery and molecular characterization of an RNA aptamer that has a length-dependent, dual functionality against AMPA and kainate receptors.…”
mentioning
confidence: 99%
See 2 more Smart Citations